Interpretasi Konsep Nusyuz Dalam Perkara Perkawinan Pada Pengadilan Agama - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
In a family life, a wife has an obligation to devote in every respect to her husband according to the Islamic Law ( article 83 Compilation of Islamic Law/KHI). This obligation is very important for a wife. If she does not do the obligation, she will be chategorized nusyuz (article 84 (I) KHI). The regulation of nusyuz in KHI is still general, without detail explanation. It makes many interpretations of judges to settle of nusyuz case. This research was done in five Religious Courts in Special Region of Yogyakarta. Data were collected by conducting interview with five judges in the Religious Courts, and it is completed by study 15 decisions about nusyuz. The data were analyzed qualitatively and then conclude it. Based on this research, we conclude that (1) Not all wife's action which does not devote in every respect to her husband is chategorized nusyuz